Emergency Medical Services Data for Cardiovascular Disease Surveillance, Program Planning, and Evaluation in Maine - Shannon DeVader, MPH; Debra Wigand, MEd, CHES; Cynthia A. Mervis, MPH; Danielle Louder; Jay Bradshaw; Kathy Decker, MPH; Katie A. Meyer, ScD, MPH (Centers for Disease Control and Prevention, 2008)
Rapid access to medical treatment is a key determinant of outcomes for cardiovascular events. Emergency medical services (EMS) play an important role in delivering early treatment for acute cardiovascular events. Attention has increased on the potential for EMS data to contribute to our understanding of prehospital treatment. Maine recently began to explore the possible role of EMS data in cardiovascular disease surveillance and cardiovascular health program planning and evaluation. We describe the Maine EMS data system, discuss findings on ease of data use and data quality, provide a sample of findings, and share how we plan to use EMS data for program planning and evaluation of community-level interventions and to partner with EMS provider organizations to improve treatment. Our objective is to increase understanding of the promise and limitations of using EMS data for cardiovascular disease surveillance and program planning and evaluation.